2017
DOI: 10.1371/journal.pone.0174328
|View full text |Cite
|
Sign up to set email alerts
|

Application of Surgical Apgar Score in intracranial meningioma surgery

Abstract: Surgical resection is the main therapeutic option for intracranial meningiomas, but it is not without significant morbidities. The Surgical Apgar Score (SAS), assessed by intraoperative blood pressure, heart rate, and blood loss, was developed for prognostic prediction in general and vascular surgery. We aimed to examine whether the application of SAS in patients undergoing craniotomy for meningioma resection can predict postoperative major complications. We retrospectively enrolled 99 patients that had underg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 21 publications
(34 reference statements)
1
6
0
Order By: Relevance
“…The effect of advanced age on post-TKA complications has also been con rmed in previous studies [11][12][13][14][15]. The complication rate after TKA increases with age [27][28][29].…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…The effect of advanced age on post-TKA complications has also been con rmed in previous studies [11][12][13][14][15]. The complication rate after TKA increases with age [27][28][29].…”
Section: Discussionsupporting
confidence: 56%
“…Studies have found that after SBTKA, the infection rate and length of hospital stay of patients are reduced, but the incidence of 90-day mortality, venous thromboembolism and neurological complications is increased [4].In addition, the risk of pulmonary embolism, cerebral embolism [5], blood transfusion rate [6,7], cardiac complications, urinary retention, and deep infection are signi cantly increased [8].At present, the comparative studies after SBTKA and staged bilateral TKA are relatively common, and many studies have provided a comprehensive assessment of complication incidence, clinical e cacy and mortality after SBTKA [4,[8][9][10].Due to the lack of established indications for SBTKA, it is always controversial to determine the age of patients, and previous studies only con rmed that patients aged 75 and above are generally not recommended to undergo SBTKA [11][12][13].Recent studies by scholars [14] also only con rmed that patients under 75 years of age and ASA1 grade or grade 2 received SBTKA, and the incidence of complications was no different from that of unilateral TKA.Regrettably, these studies did not provide further studies on the incidence of complications at various ages of SBTKA and the selection of the optimal age.For complications after TKA, some scholars used the nomograms prediction model to predict the probability of complications within 30 days after primary TKA [15].Since the incidence of complications after bilateral TKA increased signi cantly during the same period, it was necessary to establish a nomogram prediction model for complications after SBTKA and identify high-risk patients as early as possible in order to reduce the risk of postoperative complications.…”
Section: Introductionmentioning
confidence: 99%
“…The SAS is a simple formula that uses intraoperative hemodynamics and blood loss to predict postoperative complications and mortality rates 6 . The SAS was found to be positively correlated with postoperative complications and/or mortality in patients undergoing a wide variety of procedures [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] . Due to its ability to predict postoperative complications and mortality, the SAS might also be useful for the prediction of postoperative ICU admission.…”
Section: Discussionmentioning
confidence: 97%
“…The surgical Apgar score (SAS), which has been widely discussed over the past 10 years, is a simple formula that uses intraoperative hemodynamics and blood loss to predict the postoperative complications and mortality rate (Table 1 ) 6 . The SAS was positively correlated with postoperative complications and/or mortality 7 in patients undergoing vascular surgery, 8 noncardiac surgery 9 , general surgery 8 , esophagectomy 10 , colorectal resection 11 , emergency abdominal surgery 12 , elective laparoscopic cholecystectomy 13 , hepatectomy for hepatocellular carcinoma 14 , liver transplantation 15 , general oncologic surgery 8 , 16 , 17 , laparotomy gynecological surgery 18 , radical or partial nephrectomy for renal mass excision 19 , radical protectomy 20 , hip or knee arthroplasty 21 , transfemoral amputation 22 , lumbar fusion for degenerative spine diseases 23 , intracranial meningioma 24 , and head and neck cancer 13 , 25 .…”
Section: Introductionmentioning
confidence: 99%
“…Excessive bleeding hinders surgery and translates into risks for patients. [ 15 ] Recently, reports have been made using the orbito-zygomatic approach plus peeling of the middle fossa, and through a combination of extradural and intradural techniques, devascularization and SWM resection are accomplished. [ 1 14 19 ] Although such concepts are not yet neurosurgical common sense, it constitutes our view that these latter skull base techniques are fundamental to surgically resect most of SWM.…”
Section: Discussionmentioning
confidence: 99%